Responsibility and authority in management of overseas upstream investment and application for Petrovietnam - Anh, Nguyen Thi Lan; Hanh, Ngo Thi Mai; Anh, Hoang Manh; Tuan, Nham Phong (Petrovietnam Journal, 2013)
Overseas upstream investment has been executed by oil companies for many years. To ensure that the investment operations comply with local regulations as well as international petroleum practices and resources are deployed and utilised most effectively, international upstream companies have chosen and applied various models of internal management. This paper discusses ‘‘responsibility and authority’’ within a management model and compares Petrovietnam’s overseas investments with other oil companies. From an analysis of the management models of Talisman, JX NOEX, Premier Oil, Idemitsu Oil & Gas Co. Ltd, Petronas, Chevron, ONGC, Mitra Energy, BP, Santos and Petrovietnam, the authors evaluate the issue of responsibility and authority in the management of overseas upstream investments of oil companies and make some recommendations for Petrovietnam.